OVERVIEW OF RENEWABLE ENERGY SOURCES IN THE PERSPECTIVE OF CARBON FOOT PRINTING REDUCTION - DR. ANWAR M. MULLA (International Journal of Innovations in Engineering Research and Technology, 2021)
A review is done on the different methods to reduce the carbon emission ultimately thecarbon footprint in the different sectors in the perceptive of the renewablesources. Inmethodfor theRegional energy targetingalong with thesupply chain synthesisdifferent algorithmsare proposedsuch as Regional Energy Clustering (REC) for the biomass supply chains. Somemethod as are based on the scheduling the manufacturing processesin process industries soas to reduce the carbon footprint and energy consumption.